A new representative of the Hadrocheilus (Arcuatobeccus) Shimansky subgenus (rhyncholites) from the Lower Cenomanian of the South-West Crimea - V. N. Komarov; K. R. Aglutdinova; G. V. Agafonova; I. R. Huzina; E. F. Babitsky; M. A. Glukhov (Известия высших учебных заведений: Геология и разведка, 2017)
Rhyncholites of the Arcuatobeccus subgenus represent a big group, counting about 25 species and known from the Western Europe, Mountain Crimea and also San-Salvador Island. A stratigraphic distribution of the Arcuatobeccus covers an interval from the Middle Jurassic up to the Middle Cenomanian, inclusively. In the Mesozoic deposits of the Mountain Crimea, Arcuatobeccus are not popular and distributed in the section unevenly. To the last moment four Cenomanian species of Arcuatobeccus were known there. A Lower Cenomanian complex included H. (A.) alekseevi Komarov, H. (A.) ratus Shimansky и H. (A.) selbuchrensis Komarov. In the Middle Cenomanian complex, a one species of Arcuatobeccus was found - tiny H. (A.) prima Komarov. It is important to note, that the Middle Cenomanian Arcuatobeccus have not been known anywhere else in the world yet. The paper illustrates a new Lower Cenomanian species of Arcuatobeccus, found in 2017 during the Crimean training geological practice of MGRI-RSGPU. It differs from the closest species Hadrocheilus (Arcuatobeccus) selbuchrensis by a bigger size, shorter and narrower handle (in relation to the hood) and sharper, knee-like transition of the hood to the handle. The results of the detailed study of the bearlng-rock have been shown.